A Park for Renewable Energy at the State University of the Northern Rio De Janeiro - Valdo da S. Marques; Maria G. Alves; Francisca M. A. Pinheiro; Jonas Alexandre; Paulo R. N. da Silva; Alexandre M. Stumbo; Sergio N. Monteiro (The Minerals, Metals and Materials Society, 2008)
"Brazil is among the few countries with potential for developing all sources of renewable forms of energy. In particular, the country is leading the world efforts of substituting petroleum based fuels for biofuels, such as ethanol and biodiesel. Most of the Brazilian petroleum, which has now achieved self sufficiency, is extracted from offshore wells located at the north region of the state of Rio de Janeiro. In view of the future depletion of petroleum, the State University of the Northern Rio de Janeiro (UENF) has created a Center for Alternative Energies (NEAL) to carry out R&D programs on renewable forms of energy. Today, the main project of the NEAL/UENF is a model park for generation of renewable forms of energy. The objective of this work is to present the structural concept of the park and discuss its contribution in terms of scientific, technological, economical and environmental benefitsIntroductionEnergy is presently a key issue in the world agenda for sustained development and environmental protection. It is of common agreement that the existing status of increasing use of fossil fuels, mainly petroleum, natural gas and coal will not only cause depletion of these resources with a consequent elevation in price but also climate changes, especially global warming. In fact, the humankind may be already facing an irreversible situation of climate alterations as well as reduction of conventional sources of energy. The worse predictions foreseen by specialists, still for this coming century, are dramatic disasters due to catastrophic weather in association with a profound energetic crisis. This scenario may, however, be avoided by actions that could effectively tackle the core of the problem. These actions have been suggested and discussed by scientists and leading authorities, especially in international symposia [1-3]. In particular, the Kyoto Protocol proposed goals for reduction of greenhouse gas emissions as well as a mechanism of carbon credits to allow for decreasing CO2 content in the atmosphere without affecting industrial production [3]."